Eficiência de extração de cobre e níquel utilizando sistemas microemulsionados bifásicos e trifásicos - Oliveira, Mônica Rodrigues de (2014)
The environmental impact due to the improper disposal of metal-bearing industrial effluents imposes the need of wastewater treatment, since heavy metals are nonbiodegradable and hazardous substances that may cause undesirable effects to humans and the environment. The use of microemulsion systems for the extraction of metal ions from wastewaters is effective when it occurs in a Winsor II (WII) domain, where a microemulsion phase is in equilibrium with an aqueous phase in excess. However, the microemulsion phase formed in this system has a higher amount of active matter when compared to a WIII system (microemulsion in equilibrium with aqueous and oil phases both in excess). This was the reason to develop a comparative study to evaluate the efficiency of two-phases and three-phases microemulsion systems (WII and WIII) in the extraction of Cu+2 and Ni+2 from aqueous solutions. The systems were composed by: saponified coconut oil (SCO) as surfactant, n-Butanol as cosurfactant, kerosene as oil phase, and synthetic solutions of CuSO4.5H2O and NiSO4.6H2O, with 2 wt.% NaCl, as aqueous phase. Pseudoternary phase diagrams were obtained and the systems were characterized by using surface tension measurements, particle size determination and scanning electron microscopy (SEM). The concentrations of metal ions before and after extraction were determined by atomic absorption spectrometry. The extraction study of Cu+2 and Ni+2 in the WIII domain contributed to a better understanding of microemulsion extraction, elucidating the various behaviors presented in the literature for these systems. Furthermore, since WIII systems presented high extraction efficiencies, similar to the ones presented by Winsor II systems, they represented an economic and technological advantage in heavy metal extraction due to a small amount of surfactant and cosurfactant used in the process and also due to the formation of a reduced volume of aqueous phase, with high concentration of metal. Considering the reextraction process, it was observed that WIII system is more effective because it is performed in the oil phase, unlike reextraction in WII, which is performed in the aqueous phase. The presence of the metalsurfactant complex in the oil phase makes possible to regenerate only the surfactant present in the organic phase, and not all the surfactant in the process, as in WII system. This fact allows the reuse of the microemulsion phase in a new extraction process, reducing the costs with surfactant regeneration